Efeitos do ruído na saúde de funcionários de um call center na cidade de Campinas-SP - Silva, Rosy Neves da (2017)
Introduction. The work environment of the call center operator can present many health hazards. Search emphasizes only voice problems, however, there are other work-related health problems. Although the noise level is not very high, it can cause auditory and non-auditory effects Objective.To investigate the associations between noise exposure and health effects on operators of a Call Center in the city of Campinas-SP. Method. Observational and cross-sectional study carried out on212 telemarketing operators of a company in the city of Campinas, SP. The procedures included the application of two instruments: questionnaire on noise annoyance and other effects and Voice Disorder Screening Index (VDSI). The statistical analysis used as main outcome four variables: noise annoyance, stress, communication difficulties and voice complaint. The associations between the main outcome and the other variables were performed through the use of chi-square tests and a multiple logistic regress on model. Results. The sample consisted mainly of women (87.3%) and the mean age was 24.8 years. The results identified high occurrences of annoyance (77.35%), stress (75.94%), communication difficulties (71.23%), lack of attention (62.27%), irritability (58.97%) and vocal complaints (45.3%). In the total sample, more than 54% reported that environmental noise harms performance at work. In the statistical analysis of the four outcomes it was possible to identify statistically significant associations with a set of independent variables, especially those related to the presence of noise in the work environment. Conclusion. Environmental and organizational conditions and health effects were not only significantly associated, but also increased the chance of a telemarketing operator reporting noise annoyance, stress, communication difficulties and voice complaints